(untitled) (International Scientific Journal Alfraganus, 2024)
Are basically two approaches to learning the sport of karate, modern karate and traditional karate, there is no perfect approach to teaching modern karate because there are many methods of teaching modern karate in the world, teaching modern karate is Important factors must be taken into account because, unlike traditional karate, modern karate changes. Due to the large number of learning methods, a study was conducted to analyze the different teaching methods used in karate and to create a basis for defining these teaching methods. In this study, several research methods were used to collect data. Competitions are held according to the rules approved by the World Karate Federation (WKF). Among sports, karate exercises are distinguished by their complexity and unique nature. This requires conditionally paying attention to the development of all physical and mental characteristics of the athlete, mastering complex coordination techniques with your legs and hands. Unpredictable tactical situations require the constant need to make quick and effective tactical decisions. The existence of weight categories requires a strategically thought-out physiological preparation for competitions, taking certain tactical measures necessary to reduce or reduce one’s weight in a short period of time. Also, winning means the need to create effective tactics of the dispute, using the anthropometric characteristics and anthropometric characteristics of the opponent.